The Effects of Employability Skills on Entrepreneurial Intention: Parental Entrepreneurial Attitudes - Sheryl Extrikna, Chelsy; Mulawarman, Mulawarman; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2024)
Limited job opportunities are the cause of poor absorption of vocational high school or SMK graduates in the world of work, for being an entrepreneur is an alternative for them. This issue motivated the present research to examine the mediating effect of parental entrepreneurial attitudes on employability skills and entrepreneurial intention among 370 SMK students throughout South Semarang area. These numbers were sampled using the cluster random sampling technique, while their data were collected using the scales of employability skills, entrepreneurial intention and parental entrepreneurial attitude scale. Based on the findings, the effects of employability skills on entrepreneurial intention were mediated by parental entrepreneurial attitudes. The implications of this research are listed in the discussion.